Teachers’ Perspectives on English Textbook for Junior High School Students - Rahmadhani, Ahmada; Soraya, Irma; Nafiah, Marfuatin (ICONELT, 2024)
Textbooks are common and popular learning resources used in learning in Indonesia. The availability of textbooks from the government along with the development of the curriculum in Indonesia makes it interesting to investigate. This research aims to explore the perspective from MTsN 2 Sidoarjo English teachers regarding the English for Nusantara textbook for grade VIII junior high school students based on an adaptation of the quick-reference checklist from Cunningsworth (1995). This research is a qualitative descriptive study. Data was obtained from questionnaire and interview with English teachers. The results of this research show that the English teachers have a positive perspective on the English for Nusantara textbook for grade VIII.